Show me your data and I will tell you who you are: General Data Protection Regulation (GDPR) essence and aims (Economic and Political Thought, 2018)
General Data Protection Regulation (GDPR) was a response to more andmore common use of personal data in commercial transactions. The Regulationis aimed at standardising the provisions at the supranational level andincreasing consumer protection. GDPR has a potential for influence on theglobal standards and practices of personal data processing. Will the new legislationbe able to address another type of global challenges connected with theuse of big data by politicians and public authorities? Recent events, especiallythose concerning the use of advanced analysis of data in Donald Trump’selectoral campaign and the campaign of Brexit supporters’, show the need forguarantees of reliability, stability and security of democratic processes.
Keywords: GDPR, Cambridge Analytica, US elections, profiling, personality profiling, psychographics